A homoktövistermesztés, mint alternatív gazdálkodási forma - Panyor, Ágota (Jelenkori Társadalmi és Gazdasági Folyamatok, 2014)
In the short past period alternative farms are gaining more importance. In my paper, one of the potential alternatives is presented how to grow sea buckthorn. Sea buckthorn has high added value and outstanding nutritional value in processed form. The crop economy as an alternative form in the near future can play a significant role in relation to the development of economies of smaller land area.